2018
DOI: 10.1002/pca.2744
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Aqueous Extraction from Kalanchoe pinnata Leaves to Obtain the Highest Content of an Anti‐inflammatory Flavonoid using a Response Surface Model

Abstract: The optimized process is faster and spends less energy than the previous one (water; 30 min at 55°C); therefore is greener and more attractive for industrial purposes. This is the first report of extraction optimization of this bioactive flavonoid. Copyright © 2018 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
(80 reference statements)
2
30
0
Order By: Relevance
“…Applications of medicinal plants in both the prevention and treatment of chronic inflammatory diseases has been widely described in the literature (Kim et al, 2018). Specifically regarding Bryophyllum pinnatum, its use has been recognized in in vivo studies to treat some inflammatory diseases and for healing wounds (dos Santos Nascimento et al, 2018;Fernandes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of medicinal plants in both the prevention and treatment of chronic inflammatory diseases has been widely described in the literature (Kim et al, 2018). Specifically regarding Bryophyllum pinnatum, its use has been recognized in in vivo studies to treat some inflammatory diseases and for healing wounds (dos Santos Nascimento et al, 2018;Fernandes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among the constituents analyzed in B. pinnatum leaf, quercetin 3- O -α-L-arabinopyranosyl-(1→2)-α-L-rhamnopyranoside ( Bp1 ) was the first compound isolated for this specie ( Muzitano et al, 2006 ), and it is the major compound reported in literature ( Sobreira et al, 2017 ; dos Santos Nascimento et al, 2018 ). Fernandes et al (2019) and Ferreira et al (2014) reported other compounds already described for B. pinnatum : kaempferol 3- O -α-L-arabinopyranosyl-(1→2)-α-L-rhamnopyranoside ( Bp2 ) and quercetin-3- O -rhamnopyranoside ( Bp3 ).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the optimal extraction efficiency for both phenolic acids and flavonoids, response surface methodology, a valuable statistical technique was employed to optimise the sample extracting conditions. 22 After determining the range of extraction variables on the basis of preliminary single-factor test, Box-Behnken design was used to find the optimal values for three variables: liquid-solid ratio (20-60 mL/g), extraction time (20-60 min) and extraction solvent (50-100% methanol). The coded and uncoded levels of the three variables are listed in Table S2.…”
Section: Optimisation Of Sample Preparation By Response Surface Metmentioning
confidence: 99%
“…In addition, the 3-O diglycosidic bond and the dimer rhamnosearabinose are not common structure features and this flavonoid was described for few other species from different botanical families, however not as their major compound (Fernandes et al, 2019). Therefore, the compound 1 may be considered a promising chemical marker of the extract of B. pinnatum, making it also important to the conduction of deeper studies aiming to investigate its biological activities (dos Santos Nascimento et al, 2018). However, it is unknown the mechanism of action and/or some probable targets.…”
Section: Introductionmentioning
confidence: 99%